2012
DOI: 10.1152/ajpendo.00139.2012
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal secretion of death bullets: a new way of apoptotic escape?

Abstract: Ovariectomy/estrogen deficiency causes selective apoptosis of the serous epithelial cells of the submandibular glands (SMG) in female mice. Because such apoptosis does not occur in healthy, estrogen-deficient male mice, it was hypothesized that dihydrotestosterone (DHT) protects epithelial SMG cells against apoptosis. The antiapoptotic effect of DHT on human epithelial HSG cells exposed to tumor necrosis factor-α and cycloheximide was studied. Correspondingly, the proapoptotic effect of androgen deficiency was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Neither the lateral nor the medial nasal glands stain positively for lysozyme (Figure 2E,F). Medial nasal glands in FVB and Edar dlJ/dlJ mice, like the salivary glands (12), stain for cleaved caspase 3 (Figure 2G,H) but the nasopharynx glands of Edar dlJ/+  mice do not stain for cleaved caspase 3 (data not shown).
Figure 2.Nasal glands in EDA pathway deleted mice and Edar expression in adult glands.
…”
Section: Resultsmentioning
confidence: 91%
“…Neither the lateral nor the medial nasal glands stain positively for lysozyme (Figure 2E,F). Medial nasal glands in FVB and Edar dlJ/dlJ mice, like the salivary glands (12), stain for cleaved caspase 3 (Figure 2G,H) but the nasopharynx glands of Edar dlJ/+  mice do not stain for cleaved caspase 3 (data not shown).
Figure 2.Nasal glands in EDA pathway deleted mice and Edar expression in adult glands.
…”
Section: Resultsmentioning
confidence: 91%
“…In terms of the multiple and complex interactions between types of bone cells reviewed herein, further investigations are needed to fully elucidate the contents and potential modulatory roles of bone‐derived exosomes in regulating bone remodelling, especially the comprehensive protein and miRNA contents of osteoclast‐derived exosomes as well as which types of bone‐derived exosomes play dominant roles in the regulation of bone remodelling and under what circumstances they would be activated. Encapsulation by the lipid bilayer of the exosomal membrane protects proteins and miRNAs from degradation and they can be assayed in small peripheral blood samples . Thus, the different expression level of specific contents of bone‐derived exosomes might serve as a promising diagnostic and/or prognostic tool to detect early‐stage bone disorders.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…In late-phase diabetes, an increase in the number of autophagic structures occurs in granular duct cells. The histological findings from non-obese diabetic mice's submandibular gland tissues also indicate damage accompanied by massive cell infiltration [28][29][30][31]. Some studies have shown that oestrogen and progesterone regulate the structure and function of the submandibular glands.…”
Section: Discussionmentioning
confidence: 99%